2020
DOI: 10.5788/30-1-1607
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Indonesian Students' Use of Dictionaries

Abstract: This article aims to define the profile of Indonesian speakers as dictionary users by utilizing a questionnaire-based research. The survey was distributed to university students who were studying English as a foreign language. The students fall into two groups with pre-intermediate and intermediate levels of English proficiency. They were instructed to complete the survey. The question items encourage students to report their consultation frequency of dictionary use, dictionary choices and ratings, and diction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…In terms of the students' choice of dictionaries and online tools, analysis of the data indicated that the students used bilingual dictionaries more frequently than monolingual ones as well as used online dictionaries more than paper-based dictionaries. This accords with a survey finding conducted by Fallianda (2020) that pre-intermediate and intermediate students use bilingual dictionaries more often than monolingual dictionaries. The finding of this study is also consistent with those in Tong (2019), Małgorzata (2016), andDashtestani (2013) in that bilingual and online dictionaries were the most popular among the students.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In terms of the students' choice of dictionaries and online tools, analysis of the data indicated that the students used bilingual dictionaries more frequently than monolingual ones as well as used online dictionaries more than paper-based dictionaries. This accords with a survey finding conducted by Fallianda (2020) that pre-intermediate and intermediate students use bilingual dictionaries more often than monolingual dictionaries. The finding of this study is also consistent with those in Tong (2019), Małgorzata (2016), andDashtestani (2013) in that bilingual and online dictionaries were the most popular among the students.…”
Section: Discussionsupporting
confidence: 90%
“…One of the most common methods to research dictionary use is perhaps questionnaire research. Many studies in dictionary research (Fallianda 2020, Hojatpanah and Dashtestani 2020, Alhatmi 2019, Abbasi et al 2019, Chotkarnchanawat et al 2017, Aslan 2016, Boonmoh 2010 have employed this method. Although questionnaire survey research can be used as a way of obtaining results from a great number of respondents and has the potential for generating and testing a hypothesis because the large number of respondents can also mean better representation of the whole population, one basic problem associated with this type of survey as discussed by Nesi (2000) is the accuracy of responses.…”
Section: Literature Review: Uncovering Dictionary Usementioning
confidence: 99%
See 1 more Smart Citation